Exploring the putative self‐binding property of the human farnesyltransferase alpha‐subunit. Issue 21 (11th October 2017) - Hagemann, Anna; Müller, Grit; Manthey, Iris; Bachmann, Hagen S.
Abstract : Farnesylation is an important post‐translational protein modification in eukaryotes. Farnesylation is performed by protein farnesyltransferase, a heterodimer composed of an α‐ (FTα) and a β‐subunit. Recently, homodimerization of truncated rat and yeast FTα has been detected, suggesting a new role for FTα homodimers in signal transduction. We investigated the putative dimerization behaviour of human and rat FTα. Different in vitro and in vivo approaches revealed no self‐dimerization and a presumably artificial formation of homotrimers and higher homo‐oligomers in vitro . Our study contributes to the clarification of the physiological features of FTase in different species and may be important for the ongoing development of FTase inhibitors. Abstract :